2020
DOI: 10.1111/opo.12676
|View full text |Cite
|
Sign up to set email alerts
|

Myopia management in the Netherlands

Abstract: Purpose A trend that myopia is becoming gradually more common is shown in studies worldwide. Highest frequencies have been found in East Asian urban populations (96.5%) but also a study in Europe shows that nearly half of the 25‐29 year olds has myopia. With the increase in prevalence, high myopia, i.e. a spherical equivalent of ‐6 or more and an axial length of 26 mm or more is also on the rise. High myopia particularly carries a significant risk of ocular pathology related to the long axial length. This high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 101 publications
(226 reference statements)
0
50
0
4
Order By: Relevance
“…(1) Compliance may vary among studies. In Rotterdam, [35] 73% adherence to the treatment regimen was reported, which is impressive given the high doses of atropine and the related side effects. In the study in Beijing [32], parents were asked to mark the dates of medication in a calendar.…”
Section: Inconsistency Of Atropine Effect In Different Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…(1) Compliance may vary among studies. In Rotterdam, [35] 73% adherence to the treatment regimen was reported, which is impressive given the high doses of atropine and the related side effects. In the study in Beijing [32], parents were asked to mark the dates of medication in a calendar.…”
Section: Inconsistency Of Atropine Effect In Different Studiesmentioning
confidence: 97%
“…Other studies used much higher doses of atropine, for example, 0.5% atropine [34]. Recently, Klaver and Polling [35] confirmed that 0.5% atropine eye drops had been successfully used in The Netherlands now for one decade. They found a reduction in axial length growth with atropine by up to 0.2 mm/year in 74% of the children over 3 years.…”
Section: Evaluation Of the Treatment Effects Of Atropinementioning
confidence: 98%
“…Where axial biometry measures are available, these can also be informative in identifying children at risk for myopia who should be provided behavioural advice and monitored closely for the onset of myopia in order that anti-myopia therapies can be applied. 93,337,338 Percentile growth curves for White European children are available for axial length in childhood and can be used to identify patients whose eye size puts them at increased risk for future myopia. 93,337,338 In addition to identifying risk for future myopia, these centiles can be used after the onset of myopia to monitor growth trajectories with/without anti-myopia intervention.…”
Section: Management Of Premyopesmentioning
confidence: 99%
“…93,337,338 Percentile growth curves for White European children are available for axial length in childhood and can be used to identify patients whose eye size puts them at increased risk for future myopia. 93,337,338 In addition to identifying risk for future myopia, these centiles can be used after the onset of myopia to monitor growth trajectories with/without anti-myopia intervention.…”
Section: Management Of Premyopesmentioning
confidence: 99%
“…Ook wordt geadviseerd om elke dag buiten te spelen, ook als het regent, en om het beweegadvies van de Gezondheidsraad te volgen. De myopierichtlijn geeft het advies voor kinderen de 20-20-2-regel te volgen: na 20 minuten dichtbij kijken, 20 seconden in de verte kijken, plus 2 uur per dag naar buiten [ 5 ]. Uit een peiling van het Oogfonds blijkt dat kinderen deze regel duidelijk vinden en makkelijk onthouden [ 4 ].…”
Section: Leefstijladviezenunclassified